The Relationship Analysis of World Oil Price, Interest Rate, Exchange Rate and Inflation In Indonesia In The Period of 1986 – 2015 - Melyana Gita Astika; Hadi Sumarsono; Agus Sumanto (Jurnal Ekonomi dan Studi Pembangunan, 2017)
Indonesia is a developing country that has focused its monetary policy on the stability of the rupiah by putting inflation as the main goal of monetary policy. The purpose of this study was to analyze the long-term, short-term and reciprocity between world oil price, interest rate, exchange rate, and inflation. The type of research is quantitative. The data was collected using techniques of documentation that provided by the Asian Development Bank, the Federal Reserve Bank of St. Louis, World Bank, and Bank Indonesia. The analytical tool that used in this research is test the stationary of data, determining the optimum lag length, Johansen cointegration test, and estimation of Vector Error Correction Model (VECM). Based on estimates VECM can be concluded that: (1) there is a long-term relationship between world oil price, interest rate, exchange rate, and inflation in Indonesia in 1986-2015; (2) there is a short-term relationship between world oil price, interest rate, exchange rate, and inflation in Indonesia in 1986-2015; and (3) there is a reciprocal relationship between the variable interest rate and exchange rate.Keywords: World Oil Price, Interest Rate, Exchange Rate, InflationJEL Classification: E43, P44